Pengaruh Transparansi Perubahan Alokasi Dana Prodamas Guna Penyaluran Bantuan Covid-19 - Setianingsih, Novie Astuti; Asmoro, Wiwiek Kusumaning; Andari, Atik Tri (Universitas Gorontalo, 2021)
The Community Empowerment Program (Prodamas) of the City of Kediri is a program to empower the people of the City of Kediri to increase the development and income of the City of Kediri. With this Covid-19, Prodamas funds were diverted to the distribution of funds for the Covid-19 response. The purpose of this research is to test and analyze the transparency of changes in the allocation of Prodamas funds for the distribution of Covid-19 funds in the City of Kediri. The method used is descriptive quantitative by distributing questionnaires using a Liker scale which is carried out in the city of Kediri which is distributed to 46 urban villages. Research design used to test the hypothesis, in this study using a computer program SPSS 24.0 for Windows. The t-test of the effect of transparency on the distribution of Covid-19 aid funds obtained 27,528 1.971 or a p-value of 0.000 accepted at a significance level of 5% (p 0.05). This means that transparency affects the distribution of Covid-19 aid funds and Ha is declared accepted. The F test of the effect of transparency on the distribution of covid-19 aid funds obtained that Pcount is greater than Ptable, namely 1428.23 3.087 with a p-value of 0.000 accepted at the 5% significance level, meaning that the regression model is accepted, then the model of the effect of transparency on the distribution of covid-19 aid funds, Ha accepted. It was concluded that transparency had a significant positive effect on the distribution of funds for Covid-19.